2013
DOI: 10.1007/s00213-013-2966-3
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic memantine induced concurrent functional disconnectivity and altered ultra-structural tissue integrity in the rodent brain: revealed by multimodal MRI

Abstract: Our findings substantiate the hypothesis that repeated NMDA receptor blockade with nonspecific, noncompetitive NMDA antagonists may lead to functional and ultra-structural alterations, particularly in the hippocampus and cingulate cortex. These changes may underlie the behavioural effects. Furthermore, the present findings underscore the utility and the translational potential of multimodal MR imaging and acute/subchronic memantine model in the search for novel disease-modifying treatments for schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…To date, animal pharma‐RSfMRI studies have: established a link between spontaneous electrophysiological and hemodynamic fluctuations measured in rat brain by measuring EEG and BOLD signal [Liu et al, ; Nasrallah et al, ; Otte et al, ], and by pharmacological manipulation of the mitochondrial Ca ++ influx [Sanganahalli et al, ]; detected reproducible set of anatomically distinct resting‐state network from ICA of BOLD signal fluctuations in rats [Becerra et al, ] and mice [Mechling et al, ] and characterized similarities and differences between rats and mice [Jonckers et al, ], thus providing a methodological framework for standardized model‐free exploration of drug effects on the brain of different species; illustrated different patterns of resting‐state connectivity with different anesthetics (isoflurane, alpha‐chloralose and medetomidine) [Williams et al, ], or adrenergic agonists versus antagonists [Nasrallah et al, ], thus providing evidence for the sensitivity of the methods to detecting receptor‐specific effects. These findings confirm potential biases that are expected from interactions of the anesthetic drugs with the test compounds [Gozzi et al, ]. illustrated that the functional network topography [Liu et al, ], and spectral power [Magnuson et al, ] of the spontaneous fluctuation in the BOLD signal were dynamically altered by different doses of the anesthetics isoflurane and medetomidine [Nasrallah et al, ], even at different stages of coming out of anesthesia during ketamine washout [Bettinardi et al, ]; And last but not least, illustrated the efficacy of the technique in fingerprinting and pharmacological probing by providing evidence of homologous effects of an opiodergic drug, buprenorphine, in humans and in rats [Becerra et al, ], by detecting changes in the dopaminergic system after haloperidol [Gass et al, ] administration, and by detecting changes in the glutamatergic system (including hippocampus and medial prefrontal cortex) with the NMDA antagonist memantine [Sekar et al, ]. …”
Section: Experimental Objectives and Clinical Relevancesupporting
confidence: 60%
See 1 more Smart Citation
“…To date, animal pharma‐RSfMRI studies have: established a link between spontaneous electrophysiological and hemodynamic fluctuations measured in rat brain by measuring EEG and BOLD signal [Liu et al, ; Nasrallah et al, ; Otte et al, ], and by pharmacological manipulation of the mitochondrial Ca ++ influx [Sanganahalli et al, ]; detected reproducible set of anatomically distinct resting‐state network from ICA of BOLD signal fluctuations in rats [Becerra et al, ] and mice [Mechling et al, ] and characterized similarities and differences between rats and mice [Jonckers et al, ], thus providing a methodological framework for standardized model‐free exploration of drug effects on the brain of different species; illustrated different patterns of resting‐state connectivity with different anesthetics (isoflurane, alpha‐chloralose and medetomidine) [Williams et al, ], or adrenergic agonists versus antagonists [Nasrallah et al, ], thus providing evidence for the sensitivity of the methods to detecting receptor‐specific effects. These findings confirm potential biases that are expected from interactions of the anesthetic drugs with the test compounds [Gozzi et al, ]. illustrated that the functional network topography [Liu et al, ], and spectral power [Magnuson et al, ] of the spontaneous fluctuation in the BOLD signal were dynamically altered by different doses of the anesthetics isoflurane and medetomidine [Nasrallah et al, ], even at different stages of coming out of anesthesia during ketamine washout [Bettinardi et al, ]; And last but not least, illustrated the efficacy of the technique in fingerprinting and pharmacological probing by providing evidence of homologous effects of an opiodergic drug, buprenorphine, in humans and in rats [Becerra et al, ], by detecting changes in the dopaminergic system after haloperidol [Gass et al, ] administration, and by detecting changes in the glutamatergic system (including hippocampus and medial prefrontal cortex) with the NMDA antagonist memantine [Sekar et al, ]. …”
Section: Experimental Objectives and Clinical Relevancesupporting
confidence: 60%
“…These findings confirm potential biases that are expected from interactions of the anesthetic drugs with the test compounds [Gozzi et al, 2008]. illustrated that the functional network topography [Liu et al, 2013b], and spectral power [Magnuson et al, 2014] of the spontaneous fluctuation in the BOLD signal were dynamically altered by different doses of the anesthetics isoflurane and medetomidine [Nasrallah et al, 2014a], even at different stages of coming out of anesthesia during ketamine washout [Bettinardi et al, 2015]; And last but not least, illustrated the efficacy of the technique in fingerprinting and pharmacological probing by providing evidence of homologous effects of an opiodergic drug, buprenorphine, in humans and in rats [Becerra et al, 2013], by detecting changes in the dopaminergic system after haloperidol [Gass et al, 2013] administration, and by detecting changes in the glutamatergic system (including hippocampus and medial prefrontal cortex) with the NMDA antagonist memantine [Sekar et al, 2013].…”
Section: Animal Researchmentioning
confidence: 99%
“…We found that the memantine treatment enhanced the rsFC involving DMN, which has important roles in cognition, rather than the corticostriatal network that is directly involved in motor function. Interestingly, memantine treatment in healthy rats decreased cingulate, a key hub of rodent DMN, connectivity to hippocampus and prelimbic cortex, without affecting the striatum connectivity . The difference may be because MMT acted as a neuroprotective agent in hyper‐excitable diseased brain but inhibited neurotransmission in normal brain.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, memantine treatment in healthy rats decreased cingulate, a key hub of rodent DMN, connectivity to hippocampus and prelimbic cortex, without affecting the striatum connectivity. 47 The difference may be because MMT acted as a neuroprotective agent in hyper-excitable diseased brain but inhibited neurotransmission in normal brain. This also suggests that memantine may affect DMN broadly in multiple disease conditions and warrants further investigations on the mechanism and functional outcome.…”
Section: Resting-state Functional Connectivitymentioning
confidence: 99%
“…Additionally, there is evidence that increased neural activation is correlated with increased amyloid deposition, a response which may be protective in the short term (as it is thought to reduce plasticity) but damaging in the long term [63]. If this view is correct, one might then hope to use longitudinal EEG and DCM for ERP as part of a drug intervention program in which the timing and dosage of, for example, memantine [64] (which acts to reduce plasticity [65] and functional connectivity [66]) could be used to reduce these connection strengths, and so slow disease progress.…”
Section: Closing Thoughtsmentioning
confidence: 99%